Northernmost tip of South America: Giant testudinids, chelids, and podocnemidids from the castilletes formation, Colombia (2015)
Here we describe the northernmost South American record of fossil turtles from the late early Miocene to early middle Miocene of the Castilletes Formation, on the Alta Guajira Peninsula, Cocinetas basin, Colombia. Turtles in the lower segment of the Castilletes Formation (c. 16.33 Ma) are pleurodires or side-necked turtles belonging to Chelus colombiana Wood, Chelus sp., and Podocnemididae incertae sedis, and cryptodires or hidden-necked turtles attributed to Chelonoidis sp., all of them characterized by the large size of their shells, 1 meter or more total length. The middle segment of the formation (c. 14 Ma) contains specimens of Podocnemididae incertae sedis and Chelonoidis sp. The turtle fauna from Castilletes share taxa with faunas from La Venta (middle—late Miocene of Colombia), Urumaco, and Western Amazonia (late Miocene from Venezuela, Brazil, and Peru); all of these records indicate a wider geographical distribution for podocnemidids, chelids, and testudinids of tropical South America during the early to middle Miocene. The large size of the fossils described here also confirms that gigantism was characteristic of South American tropical turtles during the early Miocene, a trend that lasted at least from the Paleocene to the Pliocene in different lineages.